How children's intellectual profiles relate to their cognitive, socio-emotional, and academic functioning. (3rd July 2018) - Gubbels, Joyce; Segers, Eliane; Verhoeven, Ludo
ABSTRACT: Intellectual abilities are consistently found to be associated to child functioning. To date, however, it is unclear how varying intellectual profiles relate to differential aspects of child functioning. We screened 513 fifth-grade children on their intellectual abilities and selected three groups of gifted children, scoring in the top 10%: analytically gifted ( n  = 14), creatively gifted ( n  = 18), and analytically creatively gifted ( n  = 13). Of the remaining typically developing children, a group of 152 children was selected. We examined how these groups differed in cognitive, socio-em otional, and academic aspects of child functioning. A comparison of the gifted group as a whole versus the typically developing group, showed higher scores for the gifted group on cognitive functioning, self-concept, and academic functioning. Fine-grained group comparisons showed especially the analytical-creative subgroup to score higher than the typically developing group on visual and verbal short term memory (STM), motivation, and self-concept. Furthermore, both creatively gifted subgroups outperformed the typically developing group regarding vocabulary, while all three gifted subgroups outperformed the typically developing group regarding arithmetic. A combination of high analytical and creative abilities, which was found in 2.5% of the sample, thus seemed to lead to enhanced functioning in all three domains (i.e. cognitive, socio-emotional, and academic). Abbrevation : STM = Short term memory HSD = Honestly Significance Difference